Susceptibility of Bacteroides spp. to heavy metals. - Riley, T V (1982)
The susceptibility of 105 strains of Bacteroides to arsenate, silver, nickel, cobalt, lead, cadmium, chromium, and mercuric ions was tested by using an agar dilution technique. All strains of Bacteroides were multiply resistant. Bacteroides fragilis was significantly more resistant to silver ions than other Bacteroides species and slightly more resistant to several other ions. Arsenate was the most active ion tested, with 75% of strains being susceptible. All 25 strains of B. fragilis tested against silver sulfadiazine were susceptible.